EpigenCentral: Portal for DNA methylation data analysis and classification in rare diseases. Issue 10 (15th July 2020) - Turinsky, Andrei L.; Choufani, Sanaa; Lu, Kevin; Liu, Da; Mashouri, Pouria; Min, Daniel; Weksberg, Rosanna; Brudno, Michael
Abstract: Epigenetic processes play a key role in regulating gene expression. Genetic variants that disrupt chromatin‐modifying proteins are associated with a broad range of diseases, some of which have specific epigenetic patterns, such as aberrant DNA methylation (DNAm), which may be used as disease biomarkers. While much of the epigenetic research has focused on cancer, there is a paucity of resources devoted to neurodevelopmental disorders (NDDs), which include autism spectrum disorder and many rare, clinically overlapping syndromes. To address this challenge, we created EpigenCentral, a free web resource for biomedical researchers, molecular diagnostic laboratories, and clinical practitioners to perform the interactive classification and analysis of DNAm data related to NDDs. It allows users to search for known disease‐associated patterns in their DNAm data, classify genetic variants as pathogenic or benign to assist in molecular diagnostics, or analyze patterns of differential methylation in their data through a simple web form. EpigenCentral is freely available at http://epigen.ccm.sickkids.ca/ .